Deformations of convex real projective manifolds and orbifolds - Cho̕e, Sŏ-yŏng; Lee, Gye-Seon; Marquis, Ludovic (Arxiv, 2016)
In this survey, we study representations of finitely generated groups into Lie groups, focusing on the deformation spaces of convex real projective structures on closed manifolds and orbifolds, with an excursion on projective structures on surfaces. We survey the basics of the theory of character varieties, geometric structures on orbifolds, and Hilbert geometry. The main examples of finitely generated groups for us will be Fuchsian groups, 3-manifold groups and Coxeter groups.